Differences in impact of official development assistance on foreign direct investment by aid types - Ono, Saori; Sekiyama, Takashi (Frontiers in Political Science, 2023)
This study examined the impact of Official Development Assistance (ODA) on Foreign Direct Investment (FDI) by aid type, which has been largely overlooked in previous studies. Using the Generalized Method of Moments with a gravity model, five major donor countries (France, Germany, Japan, the United Kingdom, and the United States) and 63 recipient country pairs from 1996 to 2020 were analyzed. Granger causality tests, impulse response analyses and variance decomposition analyses using a panel vector autoregressive model were conducted to identify causal relationships in the time series and to quantitatively capture the impact. The results suggest that ODA Loans from Germany, Japan, and the United Kingdom promote FDI. Their ODA Loans have a high proportion of economic infrastructure and productive-sector support. Hence, their ODA Loans may attract FDI to recipient countries by developing infrastructure in recipient countries such as transportation, telecommunications, energy, and finance. This study contributes to an academic community by highlighting the differences of aid type in attracting FDI and provides practical implications for policymakers and practitioners in the field of international development.